Turkey: angling for position in a disintegrating world-system - Somel, Cem (Estudos Internacionais: revista de relações internacionais da PUC Minas, 2014)
Turkish national income per capita is rising relative to the world, but this is not reflected in human development indicators. Under liberal economic policies Turkey has accumulated external debt and is vulnerable to capital outflows. The Islamist party in power is mitigating the authoritarian nationalist character of the state in line with popular demand, including the Kurds’ demands for democratic rights. Assertive foreign policy in the Middle East is straining relations with the US and Israel. Interference in civil conflicts in the region may pose create dangers for domestic political stability.